The complete mitochondrial genome of the Drepane punctata (Perciformes: Drepanidae). (3rd May 2016) - Xie, Junfeng; Xie, Zhenzhen; Peng, Chen; Xu, Wen; Wang, Qing; Chen, Huapu; Li, Shuisheng; Zhang, Yong; Lin, Haoran
Abstract: The complete mitochondrial genome of the Drepane punctata was presented in our study. The mitochondrial genome is 16, 397 bp long and consists of 13 protein-coding genes, two rRNA genes, 16 tRNA genes and a control region. The gene order and composition of D. punctata mitochondrial genome was different from that of most other vertebrates. The nucleotide compositions of the light strand are 24.56% of A, 16.02% of C, 27.81% of T and 31.61% of G. With the exception of the NADH dehydrogenase subunit 6 ( ND6 ) and five tRNA genes, all other mitochondrial genes are encoded on the heavy strand.